How do new ventures in MNC ecosystems proactively overcome interfirm asymmetries? - Prashantham, Shameen; Kumar, K. (Elsevier, 2011)
Several contemporary large multinational corporations (MNCs) have developed interfirm ecosystems that are likely to attract a heterogeneous set of actors, including new ventures. New ventures are asymmetric vis-à-vis the focal MNC in terms of organisational size, structure and power which could be an impediment to the development of social capital between these sets of firms. And yet MNCs are potentially a source of novel information, opportunities and ideas. An interesting question to consider therefore is how new ventures overcome interfirm asymmetries to develop and leverage social capital with large MNCs. Our synthesis of the academic literature suggests that some new ventures are more adept than others at partnering with MNCs because they are more proactive in forming and leveraging interfirm ties with large MNCs. Insightful observations of four panellists shed light on how startups’ proactive behaviours can be vitally important in forming, consolidating and extending relationships with large MNCs.